When Higher Activations Reflect Lower Deactivations: A PET Study in Alzheimer’s Disease during Encoding and Retrieval in Episodic Memory - Bejanin, Alexandre; Viard, Armelle; Chételat, Gael; Clarys, David; Bernard, Frédéric; Pélerin, Alice; de La Sayette, Vincent; Eustache, Francis; Desgranges, Béatrice (Frontiers in Human Neuroscience, 2012)
The aim of the present study was to explore the cerebral substrates of episodic memory disorders in Alzheimer’s disease (AD) and investigate patients’ hyperactivations frequently reported in the functional imaging literature. It remains unclear whether some of these hyperactivations reflect real increased activity or deactivation disturbances in the default mode network (DMN). Using positron emission tomography (15O-H2O), cerebral blood flow was measured in 11 AD patients and 12 healthy elderly controls at rest and during encoding and stem-cued recall of verbal items. Subtractions analyses between the target and control conditions were performed and compared between groups. The average signal was extracted in regions showing hyperactivation in AD patients versus controls in both contrasts. To determine whether hyperactivations occurred in regions that were activated or deactivated during the memory tasks, we compared signal intensities between the target conditions versus rest. Our results showed reduced activation in AD patients compared to controls in several core episodic memory regions, including the medial temporal structures, during both encoding and retrieval. Patients also showed hyperactivations compared to controls in a set of brain areas. Further analyses conducted on the signal extracted in these areas indicated that most of these hyperactivations actually reflected a failure of deactivation. Indeed, whereas almost all of these regions were significantly more activated at rest than during the target conditions in controls, only one region presented a similar pattern of deactivation in patients. Altogether, our findings suggest that hyperactivations in AD must be interpreted with caution and may not systematically reflect increased activity. Although there has been evidence supporting the existence of genuine compensatory mechanisms, dysfunction within the DMN may be responsible for part of the apparent hyperactivations reported in the literature on AD.